2014
DOI: 10.1007/s11892-014-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function, Adherence, and Glycemic Control in Adolescents with Type 1 Diabetes: a Literature Review

Abstract: The aim of the present review was to examine and report findings from published research to date that has examined associations between executive function (EF), adherence, and glycemic control in youth with type 1 diabetes. A review of the published research is presented with the objectives of reporting the following: (1) the associations between EF and adherence, (2) the associations between EF and glycemic control, (3) proposed methodological considerations needed to advance related research, (4) recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 72 publications
3
78
1
1
Order By: Relevance
“…A recent review of research in T1D and EF identified the following conclusions: a relation between stronger EF and greater adherence is supported and demonstrates small to medium effect sizes ( r =0.27–0.66). However, these findings are inconsistent across studies, as some studies used different subscales or composite scores of EF or found different results based on gender [5••]. Thus, more research is needed to better understand this association.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent review of research in T1D and EF identified the following conclusions: a relation between stronger EF and greater adherence is supported and demonstrates small to medium effect sizes ( r =0.27–0.66). However, these findings are inconsistent across studies, as some studies used different subscales or composite scores of EF or found different results based on gender [5••]. Thus, more research is needed to better understand this association.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate a bidirectional relation between stronger EF skills and greater adherence ([5••] see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Youth would likely benefit most from strategies that specifically bridge the gaps common during adolescence caused by normal neuro-cognitive and emotional development. [10] Challenges in executive functioning and cognitive abilities are common among infected youth, even prior to ART initiation. [11] Further, social support, impulsivity constraining prospective planning, lability, increased needs for autonomy, and identity development need careful attention in programs focused on support YLWH.…”
Section: Introductionmentioning
confidence: 99%